1999
DOI: 10.1093/jnci/91.6.547
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Carotenoids and Vitamins A, C, and E and Risk of Breast Cancer

Abstract: Consumption of fruits and vegetables high in specific carotenoids and vitamins may reduce premenopausal breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
190
4
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(214 citation statements)
references
References 33 publications
16
190
4
4
Order By: Relevance
“…Thus, the SQ radical of the CE represents a molecular target susceptible to detoxification by dietary antioxidants such as ascorbate and might represent a defense against estrogenmediated carcinogenesis. It is interesting to note that a study following dietary intake and breast cancer risk among 83,234 women who participated in the Nurse's Health Study (NHS) concluded that consumption of fruits and vegetables high in specific carotenoids and vitamins may reduce premenopausal breast cancer risk (36). This study also showed a substantial reduction in breast cancer risk among premenopausal women who had a positive family history of breast cancer with dietary intake of carotenes, lutein͞zeaxanthin, total vitamin A, and total vitamin C from foods.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the SQ radical of the CE represents a molecular target susceptible to detoxification by dietary antioxidants such as ascorbate and might represent a defense against estrogenmediated carcinogenesis. It is interesting to note that a study following dietary intake and breast cancer risk among 83,234 women who participated in the Nurse's Health Study (NHS) concluded that consumption of fruits and vegetables high in specific carotenoids and vitamins may reduce premenopausal breast cancer risk (36). This study also showed a substantial reduction in breast cancer risk among premenopausal women who had a positive family history of breast cancer with dietary intake of carotenes, lutein͞zeaxanthin, total vitamin A, and total vitamin C from foods.…”
Section: Discussionmentioning
confidence: 99%
“…A similar protective effect for vegetable consumption was found in a meta-analysis of 14 case-control and 3 cohort studies. 31 No protective effect was found in a pooled analysis of data from 7 cohorts 32 but, in some, ascertainment of fruit and vegetable intake 33,34 was poor. Moreover, 2 of the cohorts included in this analysis have since reported protective effects for vegetable intake.…”
Section: Discussionmentioning
confidence: 99%
“…Overall number of preclinical and observational research studies regarding the role of lutein and zeaxanthin in prevention or reducing the intensity of different cancers continues to evolve from basic research as well as from human studies. These studies directed to bioavailability, metabolism, and dose-response relationships with intermediary biomarkers and clinical outcomes to determine and verify the role of lutein and zeaxanthin in controlling tumor growth in humans (Bertone et al, 2001;Boeke et al, 2014;Chew & Park, 2004;Cho et al, 2003;de Munter, Maasland, van Nkondjock & Ghadirian, 2004;Silvera, Jain, Howe, Miller, & Rohan, 2006;Wang et al, 2014;Yuan, Stam, Arakawa, Lee, & Yu, 2003;Zhang et al, 1999). Although scientific evidence in support of the beneficial role of egg yolk carotenoids in prevention or reducing the intensity of AMD and CVD and neurodegeneration are substantial, research findings about the role of egg carotenoids on different cancers are inconclusive or inconsistent and warranted further research studies, meta-analyzes, to confirm the advantageous effect of egg carotenoids.…”
Section: Cvds Oxidative Stress Alzheimer's and Cancermentioning
confidence: 99%